Lymphoproliferative disorder involving body fluid: diagnostic approaches and roles of ancillary studies - Jiwon Koh; Sun Ah Shin; Ji Ae Lee; Yoon Kyung Jeon (Korean Society of Pathologists & the Korean Society for Cytopathology, 2022)
Lymphocyte-rich effusions represent benign reactive process or neoplastic condition. Involvement of lymphoproliferative disease in body cavity is not uncommon, and it often causes diagnostic challenge. In this review, we suggest a practical diagnostic approach toward lymphocyte-rich effusions, share representative cases, and discuss the utility of ancillary tests. Cytomorphologic features favoring neoplastic condition include high cellularity, cellular atypia/pleomorphism, monomorphic cell population, and frequent apoptosis, whereas lack of atypia, polymorphic cell population, and predominance of small T cells usually represent benign reactive process. Involvement of non-hematolymphoid malignant cells in body fluid should be ruled out first, followed by categorization of the samples into either small/medium-sized cell dominant or large-sized cell dominant fluid. Small/medium-sized cell dominant effusions require ancillary tests when either cellular atypia or history/clinical suspicion of lymphoproliferative disease is present. Large-sized cell dominant effusions usually suggest neoplastic condition, however, in the settings of initial presentation or low overall cellularity, ancillary studies are helpful for more clarification. Ancillary tests including immunocytochemistry, in situ hybridization, clonality test, and next-generation sequencing can be performed using cytologic preparations. Throughout the diagnostic process, proper review of clinical history, cytomorphologic examination, and application of adequate ancillary tests are key elements for successful diagnosis.